„Symbole geben zu denken”? Theoretische und didaktische Überlegungen zur Reflexionsphilosophie Paul Ricoeurs - Marcin Morawski (Warszawskie Studia Teologiczne)
Current thinking is strongly oriented towards the logos and sees the need for demythologizing. The myth seems to belong to past forms of consciousness that belong to a "naive" worldview. Today's thinking, however, has to be based on the ratio in still in the tradition of Descartes. Based on Paul Ricoeurs' philosophy of reflection, this article aims to show that the integration of  symbolic forms like the myth but also poetry into today's thinking should not be understood as a departure from the logos, but rather as its expansion with ontological relevance. Finally, it should be explored to what extent such a way of thinking proves to be productive for educational processes.